Tradisi Mujahadah: Metode Menjaga Hafalan al-Qur'an di Pondok Pesantren al-Ittifaqiah, Indralaya, Indonesia - Muhammad Amin (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2020)
The phenomenon of memorizing scripture increasingly became the mainstream of Indonesian religious culture with the growth of various tahfidz programs and the broadcast of tahfidz events on national TV. However, Prophet Muhammad has indicated the difficulty of maintaining al-Qur'an since the 7th century AD, and it has remained nowadays. As the answer to this problem, the author conducted an ethnographic study by examining the tradition of mujahadah in Al-Ittifaqiah Islamic Boarding School with there kinds of mujahadah. Mujahadah Ula is a form of quality control on the recitation of a student by means of rotating by five coaches, mujahadah tsaniah is a form of habituation where students are required to fasting 40 days and always recite the whole al-Qur'an with memorization every day, while mujahadah tsalitsah is a form Confirmation of where students will be tested for 15 hours reciting 30 chapters of al-Quran with memorization and listened by the students and coaches in a special majlis.